A Cautionary Tale: Council Amalgamation in Tasmania and the Deloitte Access Economics Report. Issue 1 (14th April 2013) - Drew, Joseph; Kortt, Michael A.; Dollery, Brian
<x xml:space="preserve">Abstract</x> Contemporary Australian public policy has come to rely increasingly on technical reports produced by commercial consultants in contrast to the traditional approach, which employed disinterested public servants to generate the specialist information required to inform decision makers. This approach is fraught with problems, not least the fact that 'hired guns' have strong incentives to create the 'answers' sought by their employers. By way of a 'cautionary tale', this paper examines the empirical evidence adduced in favour of radical amalgamation of Tasmanian local authorities in Local Government Structural Reform in Tasmania, produced by Deloitte Access Economics (DAE) (2011), and commissioned by the Property Council of Tasmania. In particular, the paper provides a critical analysis of the econometric modelling undertaken in the DAE (2011) Report. We find that if the DAE model is re‐estimated – employing alternative functional forms – then the empirical evidence in support of Tasmania council merges evaporates.